2021
DOI: 10.1186/s12896-021-00730-6
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic degradation is an effective means to reduce aflatoxin contamination in maize

Abstract: Background Aflatoxins are carcinogenic compounds produced by certain species of Aspergillus fungi. The consumption of crops contaminated with this toxin cause serious detrimental health effects, including death, in both livestock and humans. As a consequence, both the detection and quantification of this toxin in food/feed items is tightly regulated with crops exceeding the allowed limits eliminated from food chains. Globally, this toxin causes massive agricultural and economic losses each year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…There are publications and/or news articles showcasing GMOs as the panacea for aflatoxin control. Transgenic events can lead to reduced aflatoxin levels in genetically modified maize and groundnut under controlled conditions (Thakare et al, 2017;Sharma et al, 2018;Schmidt et al, 2021) but such testing has not been done in field conditions. Programs using transgenic crops to reduce aflatoxin contamination, when and if commercially available, must know basic information about transgenes to effectively communicate with stakeholders and must provide science-based answers in a layman language to address questions on the use and safety of transgenic cultivars.…”
Section: Silver Bulletsmentioning
confidence: 99%
“…There are publications and/or news articles showcasing GMOs as the panacea for aflatoxin control. Transgenic events can lead to reduced aflatoxin levels in genetically modified maize and groundnut under controlled conditions (Thakare et al, 2017;Sharma et al, 2018;Schmidt et al, 2021) but such testing has not been done in field conditions. Programs using transgenic crops to reduce aflatoxin contamination, when and if commercially available, must know basic information about transgenes to effectively communicate with stakeholders and must provide science-based answers in a layman language to address questions on the use and safety of transgenic cultivars.…”
Section: Silver Bulletsmentioning
confidence: 99%
“…A promising post-harvest decontamination strategy involves the enzymatic conversation of aflatoxin to innocuous compounds. Prior research [20] demonstrated the successful pre-harvest degradation of aflatoxin from contaminating A. flavus conditions in developing maize kernels that were expressing an endoplasmic reticulum (ER)-targeted embryo-expressed aflatoxin-degrading enzyme isolated from the edible Honey mushroom (Armillariella tabescens) [21]. In this research, we investigate if reducing /eliminating aflatoxin by enzymatic degradation in maize kernels would also be an effective post-harvest strategy in dry stored kernels.…”
Section: Globalize Your Researchmentioning
confidence: 99%
“…Dry kernels were harvested from a control nontransgenic maize plant (Null) and three independent transgenic maize lines (Enz7, Enz8, Enz10) (Zea mays Hi II hybrid A 188 and B73 background) previously shown to be expressing an inserted aflatoxin-degrading enzyme (GenbankAccession AY941095) [20]. The inserted cassette in these transgenic maize plants consisted of a codon-optimized 2.166 kb open reading frame of an ER-targeted aflatoxindegrading enzyme expressed by an embryo-specific maize globulin-1 promoter (Genbank Accession AH001354.2) [20]. Cobs from three transgenic lines (Enz 7, Enz 8, and Enz 10) and the nontransgenic maize line (Null) were removed from ears grown in the greenhouse.…”
Section: Plant Materialsmentioning
confidence: 99%
“…In humans, AFB1 exposure has been linked to liver cancer, as well as other health problems such as immune suppression, stunted growth, and decreased cognitive function [24][25][26][27][28][29][30]. Also, OTA has been shown to cause kidney toxicity in humans, increased risk of cancer, decreased immunity, and oxidative stress [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%